Lefschetz admissible dominated spaces for maps with an inclusion property - O’REGAN, Donal (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
We consider the notion of a Lefschetz admissible dominated space and we present some fixed-point results for compact maps with a selection property. Mathematics Subject Classification (2010): 47H10, 54H25. Received 23 July 2025; Accepted 15 September 2025.